Work Life Balance and its Influence on Employee Engagement “Y” Generation in Courier Service Industry - Riyanto, Setyo; Ariyanto, Eny; Lukertina, Lukertina (International Review of Management and Marketing, 2019)
The business landscape in the courier services industry has a very significant change as a result of its high and rapid growth of e-commerce in Indonesia. The tight competition between companies in the courier service industry can greatly affect employees work life balance, especially for “Y” Generation, those born between 1979 and 1994. The purpose of the study is to determine which the factors of work-life balance of Y generation affects employee engagement in industry. The research was conducted on 118 employees from generation Y who represent each post office in Java Island. The chosen Java Island as a research location because of the number of courier companies and the largest customers, more than 50% are in Java island. The study used questionnaires to collect data. Keywords: Work Life Balance, Work Interference with Personal Life, Personal Life Interference with Work, Employee Engagement, Courier Service Industry. JEL Classification: M DOI: https://doi.org/10.32479/irmm.8499